An investigation of a method of balancing inertial loads on a slider- crank mechanism - Deiparine, Edwin O. (2007)
A machine is an assemblage of resisting bodies so arranged that it transforms motion in order to compel work. The transmission of power is being affected by the irregularities of motion due to the excess inertial loads. These are being affected by the irregularities of motion due to the excess inertial loads. These are being manifested by vibration, noise, and even fatigue problems which lead to destruction and failure. The problem of extra motion can be corrected through mass balancing. In this study, two methods of balancing the excess inertial loads; specifically on a Slider-Crank mechanism, was being investigated. The Chiou and Davies Method determines the shaking forces and moments and locates the position of the contra-rotating masses pivoted at different location to attain equilibrium on the system. The basis of location was done through analytical method using vectors and complex-algebra at different speeds of the crank. The point-mass method of balancing put equivalent masses on its linkages to be at equilibrium. The putting of masses balances the system dynamically through the kinetic analysis. The two methods were being validated through numerical examples and the result was convincing.
Keywords: Mindanao studies